Chest pain with myocardial ischemia in a child: should we think about coronary slow flow phenomenon? - Abdullah Kocabaş; Fırat Kardelen; Gayaz Akçurin; Halil Ertuğ (KARE Publishing, 2013)
The coronary slow flow phenomenon (CSFP) is an angiographic finding characterized by delayed opacification of epicardial coronary arteries in the absence of stenotic lesion. Herein, we present a 13-year-old boy with recurrent chest pain who was diagnosed with acute ST-segment elevation myocardial infarction associated with CSFP, which has not been reported previously in the pediatric age group. Coronary angiography revealed only the presence of slow flow in the left anterior descending (LAD) coronary artery. Myocardial perfusion scintigraphy revealed a reversible perfusion defect in the LAD territory, which regressed partially at rest and showed complete improvement after dipyridamole infusion. All the symptoms, electrocardiogram abnormalities and cardiac markers returned to normal after dipyridamole treatment during the follow-up. We conclude that CSFP should be kept in mind in the differential diagnosis of chest pain with myocardial ischemia in the pediatric age group.